Relevansi Dakwah Islam di Era Perkembangan Ilmu Pengetahuan dan Teknologi: Telaah Al-Qur’an dan Sunnah - Sany Nurul Aini; Annissa Salsabilla Choirutunnisa; Alihan Satra (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The development of science and technology in the modern era has brought various conveniences as well as moral challenges to human life. Rapid technological advancement is often not balanced with the strengthening of spiritual and ethical values, resulting in moral crises, disinformation, and degradation of humanity. On the other hand, Muslims still face the problem of scientific dichotomy that separates religious knowledge from general sciences. This article aims to analyze the integration of Islamic da’wah with the development of science and technology through critical and logical thinking based on the Qur’an and Sunnah. This study employed a library research method using a descriptive-analytical approach toward various Islamic and modern scholarly sources. The findings indicate that da’wah in Islam is not limited to verbal preaching but can also be implemented through professionalism, scientific development, and ethical use of technology. The integration between revelation and science needs to be carried out through an interconnected approach so that technological advancement remains within the framework of human welfare. Therefore, the mastery of science and technology grounded in Islamic values can become a relevant instrument of da’wah in building modern civilization